Analysis of Modal and Vibration Response of Gearbox of Urban Rail Train - Chen Zhongwei; 2Lu Ning; Yang Jianwei (Jixie chuandong)
The gearbox is an important urban rail train transmission equipment. Aiming at the problem of the gearbox housing easily damaged caused by the vibration,by the Creo to create the three- dimensional modeling of box and transmission components,and then using the Workbench modal analysis module,the gearbox assembly finite element analysis is carried out,and through the test modal to verify the results of theoretical modal,and through the box harmonic response analysis and random vibration analysis,the dynamic response of the gearbox is obtained. The results show that the theoretical and the natural frequency and modal test results similar formation to verify the validity of the modal obtained by the finite element method,the modal analysis and the results should be displayed to adjust the gear mesh frequency to avoid resonance frequency by adjusting the number of teeth or motor frequency. The harmonic analysis results also show that the gearbox around 500 Hz has a more noticeable vibration response,and modal analysis shows the consistency of the results. The random vibration analysis indicates that reasonable gearbox structure design can encourage good external vibration response. Based on the above analysis results,propose that the adjustment of operating strategies and optimizing the box structure design to avoid resonance effects.